Canine circovirus: An emerging or an endemic undiagnosed enteritis virus? - Gomez-Betancur, Diana; Vargas-Bermudez, Diana S.; Giraldo-Ramírez, Sebastian; Jaime, Jairo; Ruiz-Saenz, Julian (Frontiers in Veterinary Science, 2023)
Canine Circovirus (CanineCV) belongs to the family Circoviridae. It is an emerging virus described for the first time in 2011; since then, it has been detected in different countries and can be defined as worldwide distribution virus. CanineCV infects domestic and wild canids and is mainly related to hemorrhagic enteritis in canines. However, it has been identified in fecal samples from apparently healthy animals, where in most cases it is found in coinfection with other viral agents such as the canine parvovirus type-2 (CPV). The estimated prevalence/frequency of CanineCV has been variable in the populations and countries where it has been evaluated, reaching from 1 to 30%, and there are still many concepts to define the epidemiological characteristics of the virus. The molecular characterization and phylo-evolutive analyses that allow to postulate the wild origin and intercontinental distribution of the virus. This review focuses on the importance on continuing research and establish surveillance systems for this emerging virus.